PECULIARITIES OF CAREER CHOICE BY HIGH SCHOOL STUDENTS, UNIVERSITY GRADUATES AND SUBJECTS RECEIVING A SECOND HIGHER EDUCATION - L. Zajceva (Вестник университета, 2018)
The subject of the study are the characteristics of career choice at dierent stages of professional development of subjects. The author considers in detail such aspects of the topic as the primary choice and career re-selection, the prestige of the career and its traditionally male or female essence, the inuence of ideas about oneself and the self-concept on the selection process. Particular attention is paid to the theoretical and psychological development of the author denitions of characteristics and factors of career choice. The choice of career is studied in terms of its procedural characteristics, such as adequacy of independence, condence, modality and situationality